COMPARISON OF MICRO AND MACRO ELEMENT LEVELS IN THE MUSCLE TISSUES AND BLOOD ELECTROLYTES OF DIFFERENT SALMONID SPECIES - T. Karata_ (Journal of Animal and Plant Sciences, 2018)
+ + +2 +2 The purpose of this study was to investigate changes in blood electrolytes levels ( Na , K , Ca , Mg and P) and macro + + +2 +2 element (Na , K , Ca , Mg and P) and micro element ( Cu, Fe, Mn, Ni, Zn, Cd and Pb) levels in muscle tissues of the rainbow trout (Oncorhynchus mykiss), brown trout (Salmo trutta) and brook trout (Salvelinus fontinalis) grown in the + + + 2 + 2 same pond. In the study, 15 individuals of each species were randomly caught from the same pond. Na , K , Ca , Mg and P levels in blood fluid were determined by autoanalyzer Cobas C501 using commercial kits. Tissue samples were + + + 2 + 2 analyzed for Na , K , Ca , Mg , P, Cu, Fe, Mn, Ni, Zn, Cd and Pb levels, separately, by ICP-OES method. There was no significant difference between the blood electrolytes and the micro element levels of three different species. But, the + +2 + + 2 significant changes in values of Na , Mg , K , Ca and P in muscle tissues of these species were observed ( p <0.05) +2 + Highest levels of macro, micro and blood electrolyte were obtained in the rainbow trout (except Mg and K ). The size and dominance of rainbow trout when compared to the other species may be the cause of changes in the macro element levels in muscle tissues. the most that can occur in the immune system of living
Keywords: Trout; tissue; blood electrolyte; micro element; macro element.